Concept Attainment Model (CAM) in Empowering Critical Thinking Skills and Concepts Mastery for High School Students - Asy'ari Asy'ari; Wiwi Wikanta; Mulya Fitrah Juniawan (Universitas Muhammadiyah Sidoarjo, 2022)
Abstract.Existing human resources must be prepared early. Indeed, national education aims to create intelligent and competitive generations. This research is oriented towards the influence of CAM, which is implemented in the learning process. This research method is quasi-experimental. The research design used a non-equivalent control group design. As a sample is XI grade in SMA Muhammadiyah 7 Surabaya. Data collection techniques through observation and tests, critical thinking skills test sheets and students' concept mastery tests. Descriptively, self-critical thinking skills are 100% completed classically. The results of the t-test have a significance value of ≤ 0.05, which is 0.000. Then for mastery of the concept from the results of the t-test, the significance value is ≤ 0.05, namely with a significance value of 0.000. From the results of this study, it can be concluded that there is an influence of CAM p on students' critical thinking skills and students' mastery of concepts.